The Sage handbook of social marketing - Hastings, Gerard; Angus, Kathryn; Bryant, Carol A. (Sage, 2011)
"For the first time, this benchmark Handbook brings together a systematic framework and state of the art thinking to provide complete coverage of the social marketing discipline. The Handbook presents a major retrospective and prospective overview of social marketing, helping to define and shape its current and future developments by: examining the defining elements of social marketing, their intellectual origins, evolution, current status and direction of travel; discussing how these have been used in practice, emphasizing emerging areas and recent innovations; and, setting the agenda for future research and development in the discipline. For academics, this book will fill the gap in comprehensive social marketing literature, while being of interest to policymakers and graduate marketing and health studies students alike as it explores the idea that tools used to market fast-moving consumer goods and financial services can also be applied to pressing social problems, such as HIV/AIDS and global warming."--Provided by publisher.